Decomposição da lacuna de produtividade de arroz irrigado no Rio Grande do Sul - Duarte Junior, Ary José (2021)
As the largest rice producer country outside the Asian continent, Brazil can potentially contribute for future global rice supply, by sustainable intensifying cropping systems. One of the strategies to achieve this goal is by narrowing the existing yield gap (Yg) in the current farming area. However, crop yield is determined by biological limitations of the genotype, crop management practices, environmental conditions and it is necessary to understand how each one of these factors affect the yield gap. By using crop simulation models, combined with surveys and regression analysis, the rice yield potential for Rio Grande do Sul (from < 6 t ha-¹ to >14 t ha-¹), and the yield losses caused by the delay of the sowing date (0.03 t ha day-¹ from 01-sept a 13-oct, 0.08 t ha day-¹ from 14-oct to 21-dec and 0.29 t ha day-¹ after 21-dec) were estimated. Also, the yield gap in Rio Grande do Sul was estimated, resulting in 7.6 t ha-¹ (48%) of the yield potential, where 10% of the yield gap is caused by genetics (variety choice), 20% is caused by the environment (sowing date) and 70% is caused by management factors. Managements practices that can contribute for the yield gap reduction were also identified, such as crop rotation with soybeans, no-till planting system and use of lower sowing density.